Islands within islands: two montane palaeo‐endemic birds impacted by recent anthropogenic fragmentation. Issue 14 (2nd July 2015) - Robin, V. V.; Gupta, Pooja; Thatte, Prachi; Ramakrishnan, Uma
Abstract Anthropogenic habitat fragmentation of species that live in naturally patchy metapopulations such as mountaintops or sky islands experiences two levels of patchiness. Effects of such multilevel patchiness on species have rarely been examined. Metapopulation theory suggests that patchy habitats could have varied impacts on persistence, dependent on differential migration. It is not known whether montane endemic species, evolutionarily adapted to natural patchiness, are able to disperse between anthropogenic fragments at similar spatial scales as natural patches. We investigated historic and contemporary gene flow between natural and anthropogenic patches across the distribution range of a Western Ghats sky‐island‐endemic bird species complex. Data from 14 microsatellites for 218 individuals detected major genetic structuring by deep valleys, including one hitherto undescribed barrier. As expected, we found strong effects of historic genetic differentiation across natural patches, but not across anthropogenic fragments. Contrastingly, contemporary differentiation (DPS) was higher relative to historic differentiation (FST) in anthropogenic fragments, despite the species' ability to historically traverse shallow valleys. Simulations of recent isolation resulted in high DPS/FST values, confirming recent isolation in Western Ghats anthropogenic fragments and also suggesting that this ratio can be used to identifying recent fragmentation in the context of historic connectedness. We suggest that in this landscape, in addition to natural patchiness affecting population connectivity, anthropogenic fragmentation additionally impacts connectivity, making anthropogenic fragments akin to islands within natural islands of montane habitat, a pattern that may be recovered in other sky‐island systems.